Analysis of symptoms and management modalities of endometriosis in a tertiary care hospital - Khandkar, Sharvari A.; Jain, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Endometriosis is a progressive disease characterized by the growth and placement of endometrial tissue outside the uterine cavity. Endometriosis affects 10-15% of all women of reproductive age and 70% of women with chronic pelvic pain. We have aimed to study the demographic factors, symptoms and management of endometriosis. Certain risk factors are discussed which may be helpful in early diagnosis of the same. Methods: A one year hospital based retrospective study involving detailed medical records of patients presenting with endometriosis between 1st November 2022 and 31st October 2023. Results: Majority of cases of endometriosis were found in the reproductive age group. Several patients presented with multiple symptoms, of which common ones were pelvic pain, dysmenorrhea, dyspareunia and infertility. Management modalities include medical management using GnRH agonist like injection leuprolide and surgical management techniques involving laparoscopy and laparotomy depending upon the extent of involvement. The most common site of endometriosis was found to be the ovary, while other peroperative findings included distorted anatomy and a concomitant infective focus owing to pelvic inflammatory diseases. Conclusions: Endometriosis can decrease quality of life due to severe pain, fatigue, infertility. No preventative measures have yet been found. But early diagnosis and management may be extremely helpful in improving the quality of life.